2012
DOI: 10.1037/a0025169
|View full text |Cite
|
Sign up to set email alerts
|

Would introverts be better off if they acted more like extraverts? Exploring emotional and cognitive consequences of counterdispositional behavior.

Abstract: People enjoy acting extraverted, and this seems to apply equally across the dispositional introversion-extraversion dimension (Fleeson, Malanos, & Achille, 2002). It follows that dispositional introverts might improve their happiness by acting more extraverted, yet little research has examined potential costs of this strategy. In two studies, we assessed dispositions, randomly assigned participants to act introverted or extraverted, and examined costs-both emotional (concurrent negative affect) and cognitive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
164
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(191 citation statements)
references
References 65 publications
22
164
2
3
Order By: Relevance
“…In a seminal study, Fleeson et al () showed that when people were experimentally instructed to behave in either an extraverted or introverted way, acting extraverted made them happier as compared to acting introverted. This result has since been replicated in several other studies employing both experimental and ESM methodologies (e.g., McNiel, Lowman, & Fleeson, ; Wilt et al, ; Zelenski et al, ). Thus, there is mounting evidence for a causal relation between extraverted behavior and positive mood.…”
Section: The Consequences Of Personality States In Everyday Lifesupporting
confidence: 55%
“…In a seminal study, Fleeson et al () showed that when people were experimentally instructed to behave in either an extraverted or introverted way, acting extraverted made them happier as compared to acting introverted. This result has since been replicated in several other studies employing both experimental and ESM methodologies (e.g., McNiel, Lowman, & Fleeson, ; Wilt et al, ; Zelenski et al, ). Thus, there is mounting evidence for a causal relation between extraverted behavior and positive mood.…”
Section: The Consequences Of Personality States In Everyday Lifesupporting
confidence: 55%
“…Several researchers have suggested that acting extraverted could be an effective intervention for increasing an individual's levels of PA (e.g., Blackie, Roepke, Forgeard, Jayawickreme, & Fleeson, 2014). Although introverts do not appear to find it distressing, effortful, or inauthentic to act extraverted in the short-term (e.g., Fleeson & Wilt, 2010;Gallagher et al, 2011;McNiel et al, 2010;Zelenski et al, 2012), extraverted behavior may be related to delayed fatigue for introverts and extraverts alike (Leikas & Juhani-Ilmarinen, 2016). There may also be other reasons why introverts may be reluctant to act extraverted to increase their PA. For example, introverts may underpredict how enjoyable acting extraverted can be (Zelenski et al, 2013), and an emerging cultural movement aims to celebrate introverts "for who they are" (Cain, 2012; http://www.quietrev.com).…”
Section: Strengths Limitations and Implicationsmentioning
confidence: 99%
“…Several experimental studies have provided causal evidence that participants who are instructed to act extraverted (e.g., talkative, bold, assertive) report higher levels of PA than those instructed to act introverted (e.g., quiet, passive, reserved) during interactive activities in the lab (Gallagher, Fleeson, & Hoyle, 2011;McNiel & Fleeson, 2006;McNiel, Lowman, & Fleeson, 2010;Smillie, Wilt, Kabbani, Garratt, & Revelle, 2015;Zelenski et al, 2013;Zelenski, Santoro, & Whelan, 2012) (Keyes, 1998) explained 32% of the relation between trait extraversion and PA. Of the five subscales, social contribution (believing that one has something valuable to give, and does give, to society) was the strongest mediator, independently explaining 29% of the trait extraversion-PA relation. To bolster this correlational study with experimental evidence, Smillie, Wilt, and colleagues (Study 2) then investigated whether state measures of social well-being and social contribution mediated the relation between enacted extraversion and increased PA. As a state measure of social contribution, participants reported the percentage to which they "contributed to the discussion tasks", relative to the other two participants.…”
mentioning
confidence: 99%
“…We wish to examine whether the goals people are pursing at any given moment can predict both differences between people in how extraverted they are and differences within people in how extraverted they are being (Heller, Komar, & Lee, 2007; Zelenski, Santoro, & Whelan 2011). Using experience-sampling methodology, we asked participants to report their momentary goal pursuit and state extraversion over ten days.…”
mentioning
confidence: 99%